Words, Sense, and Denotation Meaning in Pupuh Ginanti “Saking Tuhu Manah Guru” - Widiadnya Putri, I Gusti Ayu Vina; Santika, I Dewa Ayu Devi Maharani; Winartha, Ida Bagus Gde Nova (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2024)
This study aims to analyze words, sense, and denotation in Pupuh Ginanti, entitled